Influence of duration of dietary vitamin E supplementation on swine growth performance and carcass quality - J F Stika; John A Unruh; Donald H Kropf; Melvin C Hunt; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1998)
Supplementing medium-lean genotype pigs with supranutritional concentrations of dietary vitamin E (91 IU d-a-tocopheryl acetate/lb of feed) for as long as 70 d during the finishing phase was not effective in improving swine performance, feeding characteristics, and 24 h loin muscle quality. However, lower carcass temperatures obtained by spray chilling pork sides at OÂ°C versus 4.4Â°C had a beneficial effect on 24 h carcass quality by improving marbling and lean firmness scores and reducing loin muscle moisture exudate. Overall, 24 h pork carcass quality was impacted more by chill rate than dietary vitamin E supplementation.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Pork; Vitamin E; Chill rate